2020
DOI: 10.4049/jimmunol.2000326
|View full text |Cite
|
Sign up to set email alerts
|

Seletalisib for Activated PI3Kδ Syndromes: Open-Label Phase 1b and Extension Studies

Abstract: Mutations in two genes can result in activated PI3Kd syndrome (APDS), a rare immunodeficiency disease with limited therapeutic options. Seletalisib, a potent, selective PI3Kd inhibitor, was evaluated in patients with APDS1 and APDS2. In the phase 1b study (European Clinical Trials Database 2015-002900-10) patients with genetic and clinical confirmation of APDS1 or APDS2 received 15-25 mg/d seletalisib for 12 wk. Patients could enter an extension study (European Clinical Trials Database 2015-005541). Primary en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
(55 reference statements)
0
15
0
Order By: Relevance
“… 35 A phase 3 trial of the oral inhibitor seletalisib was terminated; 36 published phase 1b and open label extension studies describe moderate efficacy and AEs that led to treatment discontinuation. 37 The reasons behind the differences in efficacy and tolerability between seletalisib and leniolisib are not immediately clear but may involve inhibitor structure and isoform selectivity.…”
Section: Discussionmentioning
confidence: 99%
“… 35 A phase 3 trial of the oral inhibitor seletalisib was terminated; 36 published phase 1b and open label extension studies describe moderate efficacy and AEs that led to treatment discontinuation. 37 The reasons behind the differences in efficacy and tolerability between seletalisib and leniolisib are not immediately clear but may involve inhibitor structure and isoform selectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Third, it allowed the initiation of immunoglobulin substitution and azithromycin administration to prevent respiratory infections and bronchiectasis, which are a frequent complication of APDS (17). The diagnosis of APDS will also provide a future benefit for the patient as it will expand the therapeutic options when novel specific treatments for APDS (e.g., specific PI3K inhibitors such as leniolisib or seletalisib) become available (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an open label phase 1b study on Seletalisib ( 60 ) demonstrated an acceptable safety profile and positive effects on several clinical features and disease activity in patients with APDS1 and APDS2.…”
Section: Targeted Therapiesmentioning
confidence: 99%